STUDI PERENCANAAN STRUKTUR GEDUNG HOTEL 7 LANTAI DI JEPARA - Natalius, Natalius; Umam, Khotibul; Rochmanto, Decky; Qomaruddin, Mochammad; Zuslah, Risqi Amar; Prasetyo, Dimas Adi; Wicaksono, Caesar; Fahmi, Nirzam Tri Agus (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
The development of the tourism sector in Indonesia has positively contributed to the growth of hotel construction as a key accommodation facility. In densely populated urban areas, multi-storey hotel buildings are required to efficiently meet temporary housing demands. This study presents the structural design of a seven-storey hotel building located in Jepara. The structure is designed using reinforced concrete, with a concrete compressive strength of 30 MPa. Reinforcement steel with yield strengths of 400 MPa and 240 MPa is adopted. Floor slabs are designed with a thickness of 120 mm, while the roof slab has a thickness of 100 mm. The main beams have dimensions of 700 × 400 mm for floors 2–4 and 700 × 300 mm for floors 5–7, while secondary beams measure 500 × 350 mm. Columns are designed with dimensions of 800 × 800 mm. The foundation system consists of bored piles with a diameter of 600 mm, including pile caps of varying configurations. Staircases are designed with a tread width of 25 cm and a riser height of 20 cm. The building is equipped with an elevator with a capacity of 600 kg (11 persons).